Pengaruh profitabilitas dan ukuran perusahaan serta kepemilikan manajerial terhadap pengungkapan corporate social responsibilty (pada perusahaan pemenang penghargaan isra dan go public di bei 2011-2014) - Fitriani Fitriani; Djoko Setyadi; Rizky Yudaruddin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of the research is to find out the impact of the profitabilitas (ROA), firm size. The purpose of the research is to find out the impact of the profitabilitas (ROA), firm size (SIZE) and managerial ownership (MOWN) to the corporate social responsibility (CSR) disclousure. The data was used secondary data obtained from the company’s financial statements and annnual report in the all sector of the winner ISRA anf go public in 2011-2014 periods in Indonesia Stock Exchange (www.idx.co.id). The population data this study is all sector company of the winner ISRA and go public in the Bursa Efek Indonesia in 2011-2014 and the sample of 16 companies using purposive technique sampling. The analytical tool used in this research was deskriptive statistical analysis, hypotesis test and classic assumptions test. The result of the research show that the hypotesis test profitability and firm size has significant positive effect on the corporate social responsibility disclousure. Managerial ownership significant negative effect on the corporate social responsibility disclousure. (SIZE) and managerial ownership (MOWN) to the corporate social responsibility (CSR) disclousure. The data was used secondary data obtained from the company’s financial statements and annnual report in the all sector of the winner ISRA anf go public in 2011-2014 periods in Indonesia Stock Exchange (www.idx.co.id). The population data this study is all sector company of the winner ISRA and go public in the Bursa Efek Indonesia in 2011-2014 and the sample of 16 companies using purposive technique sampling. The analytical tool used in this research was deskriptive statistical analysis, hypotesis test and classic assumptions test. The result of the research show that the hypotesis test profitability and firm size has significant positive effect on the corporate social responsibility disclousure. Managerial ownership significant negative effect on the corporate social responsibility disclousure.